Extrinsic Motivation of Students at SMA Negeri 3 Luwu to Learn English from Home - Afrilia AS; St. Asriati AM; Ariana Ariana; St. Asmayanti AM (Celebes Journal of Language Studies, 2022)
This study used qualitative research that consisted of ten students from senior high school in Luwu. To determine the extrinsic motivation when the students learn from home, the students answered the interview that consisted of ten items. The study discovered that learning English at home makes children sluggish and that their drive to learn lowers due to their surroundings, teachers, and parents. On the environmental side, disruptions at home, such as the sound of chickens, televisions, car horns, or the unsettling sounds of motorcycles, are common when beginning lessons. On the teacher's side, most teachers give students assignments without thoroughly explaining the material, causing students to be sluggish about taking home lessons, particularly in English subjects. Because they are lazy, teachers are ineffective at carrying out their responsibilities by satisfying the needs of children. Physiological demands, the market to be accepted and loved, the need for self-esteem, and the need for self-realization are all examples. When studying at home, their children's interest in learning is stifled by the lack of parental attention. Children feel abandoned when their parents are preoccupied with their professions. Parents and families must be there for this condition, especially during the learning period. The necessity of parents and families to participate actively in their children's education is vital, especially during a pandemic when teachers and educational facilities are restricted.